중고등학교 영어 온라인 수업에서의실재감과 학업만족도* - 김형준; 김현옥 (담화와 인지, 2023)
This study examined middle and high school students’ perceptions in the online English learning environment, focusing on their sense of teaching presence, cognitive presence, social presence, and overall satisfaction. The study also pursued how different types of presence interact with students’ background variables. A questionnaire was administered to 102 participants, comprising 30 middle school and 72 high school students. Results indicated that cognitive presence was the highest, while social presence was the lowest. Notably, there was a significant group difference in social presence, with middle school students displaying greater social presence than their high school counterparts. Correlation analyses demonstrated that all three types of presence were significantly linked to students’ overall satisfaction for both middle and high school students and that cognitive presence was positively related to the students’ academic achievement. When both groups were analyzed separately, teaching presence had a more pronounced impact on high school students’ satisfaction, while social presence played a more crucial role for middle school students. The findings underscored the need for tailored online course design, incorporating differentiated teaching strategies based on school grades to enhance the sense of presence in learning, thereby fostering increased students’ engagement and improved academic performance.
Keywords: online learning; e-learning; teaching presence; cognitive presence; social presence; academic satisfaction; secondary education